Hubungan Perilaku Ibu dalam Penggunaan Botol Susu dengan Kejadian Diare pada Balita - Rifiana Hikmawati; Metti Verawati (STIKes Patria Husada Blitar, 2015)
Introduction The wrong way to use a bottle of milk can cause bacteria to grow. Of the growth of bacteria in a bottle can interfere with the babyâ€™s digestive system, it can even cause diarrhea in infants or toddlers. The aim of this study were: to analyze the relationship maternal behavior in the use of bottles of milk with diarrhea. Methods, research design used in the study is correlational and cross sectional approach. To determine the relationship of maternal behavior in using milk bottle with incidence of diarrhea in infants with a nominal scale can be searched by using the Chi-Square Test Statistics. Results, Results of chi square analysis obtained x2 x2 count of 4.6 and Table 3.84. So count eâ€ x2 of x2 tables acceptable means Ha Ho is rejected, it shows no association between maternal behavior in the use of the bottle with the incidence of diarrhea in infants. Discussion, hoped for the nursing profession not only serve the clinical aspects (curative and rehabilitation), but needs to be developed for promotive and preventive efforts in an attempt to prevent the occurrence of diarrhea